Skeletal Muscle Involvement in B-Cell Lymphoma: Two Cases Illustrating the Contribution of Imaging to a Clinically Unsuspected Diagnosis. (30th April 2017) - Burton, Elijah; Schafernak, Kristian; Morgan, Elaine; Samet, Jonathan
Abstract : Skeletal muscle lymphoma is rare, comprising only a very small subset of lymphoma cases. There are characteristic imaging features which, if recognized, can prevent delay in diagnosis and treatment, particularly when not suspected clinically. Herein, we report two cases of skeletal muscle lymphoma with nearly identical imaging features; the first is an example of primary muscle lymphoma in a 17-year-old boy with back and thigh pain, and the second represents lymphoma recurrence in a 55-year-old man with HIV. Characteristic features seen on MRI were key in raising suspicion for the disease and helped prevent a delay in pathologic diagnosis.